2021
DOI: 10.3389/fmicb.2021.763296
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Klebsiella pneumoniae in Drainage Fluid After Pancreaticoduodenectomy: Risk Factors and Clinical Impacts

Abstract: To investigate the risk factors and clinical impacts of the occurrence of Klebsiella pneumoniae isolated from drainage fluid in patients undergoing pancreaticoduodenectomy (PD). Clinicopathological data of all patients who underwent PD from January 2018 to March 2021 were analyzed retrospectively. The univariate and multivariate analyses were performed to identify independent risk factors for the occurrence of K. pneumoniae in drainage fluid and its clinical impacts on postoperative complications. Of the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…In our study, 54.3% of the patients were jaundiced and 65% of them received preoperative biliary drainage, undoubtedly contributing to the high postoperative SSI rate. Significantly, K. pneumoniae and E. faecalis were frequently found in postoperative ascites and bile in the Fu study, and we further confirmed these findings in our earlier research that positive bacteria cultures, particularly K. pneumoniae, were closely related to CR-POPF and serious complications [22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, 54.3% of the patients were jaundiced and 65% of them received preoperative biliary drainage, undoubtedly contributing to the high postoperative SSI rate. Significantly, K. pneumoniae and E. faecalis were frequently found in postoperative ascites and bile in the Fu study, and we further confirmed these findings in our earlier research that positive bacteria cultures, particularly K. pneumoniae, were closely related to CR-POPF and serious complications [22].…”
Section: Discussionsupporting
confidence: 90%
“…7 [34.8-39.4] g/L vs. 38.4 [36.4-40.5] g/L; p = 0.013) and higher CRP level (6.5 [4.2-34.6] g/L vs. 4.7 [2.9-9.8] g/L; p = 0.007) (Table 3). The incidences of CR-POPF (53.2% vs. 31.7%; p = 0.016), major complications (36.2% vs. 4.8%; p = 0.001), PLOS (22 [17-33] d vs. 17 [14][15][16][17][18][19][20][21][22][23] d; p = 0.002), and CCI score (34.8 [24.2-39.2] vs. 25.7 [19.4-32]; p = 0.001) were all increased in sarcopenic patients. Significant sex differences were found in the visceral obesity group (33 men vs. 5 women; p = 0.001) and the BMI was higher (26.1 ± 3.5 kg/m 2 vs. 22.1 ± 2.4 kg/m 2 ; p = 0.001).…”
Section: Relations Between Clinical Characteristics and Body Morphome...mentioning
confidence: 99%
“…Given that organ/space SSI is the most frequent cause of postoperative complications, which may trigger subsequent events such as CR-POPF, sepsis, readmission or even death, this retrospective study's ndings are notable. As we reported previously and showed in this study, PBD was substantially corelate with postoperative infectious complications especially organ/space SSI [2,11,19]. This invasive operation destroys the function of Oddi's sphincter, increase the contamination of surgical eld with bile which may contain microbes resistant to ceftriaxone after the resection of common bile duct [20,21].…”
Section: Discussionsupporting
confidence: 62%
“…This speculation is supported indirectly by the fact that a number of studies had demonstrated that speci c antibiotic based on bile culture was effective on reducing the incidence of organ/space SSI[26-28]. We identi ed K. pneumoniae had negative impacts on organ/space SSI, major complications, CR-POPF based on past research [11]. The study focused on the anastomoses of the digestive tract had implicated collagenase-producing pathogens, such as Enterococcus, in the formation of anastomotic leakage which may result in subsequent organ/space SSI [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation